Impact of non-monetary and low monetary inputs on yield and economics of brown sarson (Brassica campestris L.) under temperate hill ecology: IMPACT OF INPUTS ON YIELD AND ECONOMICS OF BROWN SARSON - T MUBARK; A SHAKOOR; PARVEZ A SHEIKH; HASEEB-UR-REHMAN (Journal of Oilseeds Research, 2022)
India imports vegetable oil to meet the domestic demand, which indicates that there is a dire need to improve the oilseed production through effective technology dissemination. To narrow down the yield gaps and achieve maximumyields, demonstrations on improved technologies related to brown sarson were conducted at 133 locations from 2016 to 2021 by the Krishi Vigyan Kendra in Kulgam district, Kashmir. The results revealed a significant improvement in yield with improved practice (IP) over farmers practice (FP). IP recorded an average yield of 13.2q/ha with a yield superiority of 28 % over FP (10.3 q/ha). The extension gap, technology gap and technology index were 2.8q/ha, 2.9q/ha and 16.4%, respectively. Though input costs were higher by ` 1309/ha, but, the net returns were higher by ` 10693/ha in IP over FP. Further, the B:C ratio was also higher in IP (2.1) as compared to that of FP (1.6).